Impacts of additive manufacturing on supply chain flow: A simulation approach in healthcare industry - Eren Özceylan; Cihan Çetinkaya; Neslihan Demirel; Ozan Sabırlıoğlu (Logistics, 2018)
Additive manufacturing (AM) can lead to innovative solutions in traditional supply chain networks (TSCN), which contains very complicated and -hard to manage- chains. With 3D printing technology, a design file can transform directly to a product, skipping many traditional manufacturing steps. Thus, this new application can affect all logistics and supply chain activities positively. The research problem of this paper is to search and assess supply chain changes associated with 3D printing technology adoption to identify the potential impact of AM. To do so, two different supply chain networks, which are TSCN and 3D printing supply chain network (3DPSCN) for healthcare industry are considered. A simulation model is developed to evaluate the potential impact of 3D printing improvements on the configuration of orthopedic insole supply chains. The main contribution of this paper is proposing a simulation model for a healthcare company to compare its 3DPSCN structure with its TSCN version. The results show the concrete benefits such as lead-time and number of customers that can be achieved by 3DPSCN compared to TSCN.
Keywords: 650; 3D printing; additive manufacturing; orthopedic insole; simulation; supply chain